Differentiation of reservoir sediment inflow forecasting using RUSLE-SDR, Rainfall - Runoff - Sediment Discharge Rating Curve (RR-SRC) and SWAT - Abdul Razad Z.; Azwin.razad@tnb.com.my; Sidek L.M.; Basri H.; Jung K.S. (Mattingley Publishing, 2023)
Catchments; Discharge (fluid mechanics); Forecasting; Hydroelectric power; Rain; Sediment transport; Sedimentation; Surveys; Rainfall runoff; Reservoir sedimentation; Sediment delivery ratio; Sediment yields; Soil loss; SWAT; Runoff